A Bamboo-Hybrid-Slat Laminate of Fishing Boat: Materials Selection, Scantling Calculation and Construction Cost - Supomo, Heri; Djatmiko, Eko Budi; Supomo, Wikaranosa; Permana, Rizki Dian (Department of Naval Architecture - Diponegoro University, 2021)
Abstract. Bambusa Arundinacea slat lamination has relatively high tensile and flexure strength, while Pterocarpus Indicus has relatively lower than. These two types of bio-materials are very cheap, easy to cultivate, fast growing, and renewable material. For this reason, hybrid slats lamination of Bambusa Arundinacea and Pterocarpus Indicus was chosen as a construction material for fishing boats to substitute solid Teak wood which is increasingly rare and expensive. Based on the results of the tensile and flexural strength tests show that the configuration of the hybrid laminated with the parallel slats has the highest tensile strength (114.636 MPa) and flexural strength (111.606 MPa). These two strength values are used to calculate the 20GT fishing boat scantling in accordance with the Indonesian Classification Bureau vol vii 2013 regulations. By using the hybrid lamination material of Bambusa Arundinacea - Pterocarpus Indicus slats, the scantling of 20GT fishing boat will be slightly smaller, the volume of material needed is 28.7% lower and the construction cost 40.66.% less than Teak wood material.